ИРОДАВИЙ СИФАТЛАРНИНГ ЁШ БИЛАН БОҒЛИҚ ЎЗГАРИШЛАРИ - Жумабаев, Т.Ж. (SCIENCE and SOCIETY, 2022)
In this paper, age-related changes in willpower traits are discussed from the perspective of some scholars. In particular, analyzes were conducted on some volitional qualities related to age.